(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Decay and spectroscopic properties of vector and scalar diquarks have been studied. The decay widths and decay constants of scalar and vector diquarks have been estimated in the frame work of quasi particle model of diquark. The decay widths of exotic baryons like,Î”, N, Î¸+ have been investigated. The investigation is important in the view of LHC era where existence of new particle (new Physics) are expected including the colored objects like diquarks. The results obtained are compared with existing theoretical and experimental works wherever available. Some interesting observations are made.